Improvement of Fertility in Postpartum Anoestrus Buffaloes by using Different Hormonal Protocols during Non Breeding Season - Patil, AD; Shastpure, AK; Jadhao, PD; Korde, JP; Patil, MS; Patil, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was conducted on 40 postpartum anooestrus buffaloes randomly divided into four equal groups during non-breeding season. The buffaloes were selected based on ovarian inactivity, good body condition score and overall good health. Group I was administered Ovsynch protocol + Progesterone impregnated intravaginal device (PRID). Group II was administered PRID which was removed on 7th day and GnRH 10 µg i/m was given on day of AI. Group III was administered Ovsynch protocol and Group IV was kept as untreated control. 100, 80, 80 and 00 % animals responded in groups I, II, III and IV respectively. Fix timed AI was performed in all responded buffaloes. Calcium, phosphorous, cholesterol and protein level increased (p
Keywords: Buffaloes; Anooestrus; Hormonal protoco; Fertility improvement.